1994
DOI: 10.1039/an9941901283
|View full text |Cite
|
Sign up to set email alerts
|

Wide-spread and systematic errors in the analysis of soils for polychlorinated biphenyls. Part 2. Comparison of extraction systems

Abstract: The various factors in the separation of polychlorinated biphenyls from soil for determination by gas chromatography were compared using data from an interlaboratory study, including extraction equipment, solvents and clean-up procedures. These were compared for accuracy and precision using five soils spiked with Aroclor 1260 at concentrations covering a range of four orders of magnitude. Results from laboratories using Soxhlet extraction were significantly more accurate than those obtained using sonication, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The abundance of highly chlorinated congeners decreases while those of lower chlorinated, ortho-substituted, congeners increases by the preferential removal of meta-and parasubstituted chlorines. Since the meta and para chlorines are removed with anaerobic dechlorination, the concentration of coplanar congeners with dioxin-like toxicity is reduced [21,54,55]. Moreover, all of the tri-and tetra-chlorinated dechlorination products detected in this study are substrates for ring cleavage by a variety of aerobic microorganisms [7,18,44,45], indicating that reductive dechlorination of A1254 has the potential to promote further degradation by aerobic microorganisms.…”
Section: Pathways Of A1254 Dechlorinationmentioning
confidence: 87%
“…The abundance of highly chlorinated congeners decreases while those of lower chlorinated, ortho-substituted, congeners increases by the preferential removal of meta-and parasubstituted chlorines. Since the meta and para chlorines are removed with anaerobic dechlorination, the concentration of coplanar congeners with dioxin-like toxicity is reduced [21,54,55]. Moreover, all of the tri-and tetra-chlorinated dechlorination products detected in this study are substrates for ring cleavage by a variety of aerobic microorganisms [7,18,44,45], indicating that reductive dechlorination of A1254 has the potential to promote further degradation by aerobic microorganisms.…”
Section: Pathways Of A1254 Dechlorinationmentioning
confidence: 87%
“…Majid et al have compared n-hexane (nonpolar; ε: 1.89 at 20 ℃) and n-hexane/acetone (polar; ε: 21.01 at 20 °C) mixtures, and higher extraction efficiency was obtained using the mixture of n-hexane/acetone for Aroclor 1016 contaminated soil [16] . Kimbrough et al have demonstrated that polar solvents were superior to nonpolar solvents in both Soxhlet extraction and ultrasonic extraction for PCBs removal from contaminated soils [51] .…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no basic rules for selecting organic solvents in soil washing for the remediation of nonpolar pollutants such as PCBs and dioxins have been suggested owing to highly complicated soil systems and pollutants characteristics. However, some studies have provided clues for the necessity of polar solvents—1) soil, such as clay and soil organic matter, can be negatively charged; 2) the attraction for water increases as the size of soil particles decreases; 3) soil with higher organic content has higher water-holding capacity; and 4) water content in soil inhibits the contact between pollutants in soils and nonpolar solvents [4] , [14] , [51] , [52] , [53] . In this study, the water content in the soil was less than 0.15 %, and the proportion of clay was 20.6 % in the soil texture.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonication method has been used for soil and sediment samples in previous studies (Hadnagy et al, 2007; Kimbrough et al, 1994). Extraction efficiency of ultrasonic method was very low (40 to 55%, data not shown) because during the extraction, some of solids in the samples stuck to the ultrasonic probe, leading to sample loss.…”
Section: Resultsmentioning
confidence: 99%